PELATIHAN PEMBUATAN PAKAN ALTERNATIF DARI SISA HASIL PERTANIAN - Umbang Arif Rokhayati; Nibras Karnain Laya; Sry Yenny Pateda (Jambura Journal of Husbandry and Agriculture Community Serve (JJHCS), 2022)
The purpose of this community service activity is to increase the knowledge and skills of the Limbatihu Village community in making alternative animal feed from banana gedebok. The specific target to be achieved is to increase livestock production through the provision of fermented feed from banana stems. Provision of alternative feed from the banana tree is expected to increase the body weight of livestock in a short time. This program also aims to utilize agricultural residues that can be used as alternative animal feeds that contain high crude fiber and nutrients. The method used in community service is to empower the community through simulations and demonstrations. The main target is the farmers in Limbatihu Village. Based on direct observation, it can be seen that the farmers in Limbatihu Village are quite enthusiastic in making fermented banana gedebok as an alternative to animal feed. Key words : Fermentation, Banana Gedebok and Livestock